Analisis Solvabilitas Terhadap Kinerja Keuangan Pada Bank Mandiri Tahun 2016-2019 - Alya Dewanti Permatasari; Natania Anggraini; Nur Emily Tasmiatun; Renny Oktafia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research was conducted with the aim of analyzing the financial performance of PT Bank Mandiri (Persero) Tbk using solvency ratios with indicators. The method used in this research is qualitative descriptive analysis. The research results show that PT Bank Mandiri's financial performance tends to fluctuate, in terms of the NPM profitability ratio which is in very good condition and ROA which is in poor condition. Judging from the solvency ratio, DER and DAR are in poor condition. The results of this research are in line with Meutia Dwi (2017) who stated that the solvency ratio is in poor condition. Therefore, it is hoped that PT Bank Mandiri (Persero) Tbk can maintain financial performance and increase company profits so that the company is able to pay short-term and long-term debt.